First record of Stegomyia albopicta (Skuse) (Diptera: Culicidae) in Germany. Issue 26 (2008) - Pluskota, Björn; Storch, Volker; Braunbeck, Thomas; Beck, Matthias; Becker, Norbert
No abstract available